Selection of Treatment Method for Repeated Removable Denture Prosthetics - Gurskaya Нарміна Азад (Actual Dentistry, 2025)
Abstract. The majority of patients do not adhere to the recommended use periods for removable prosthetic appliances and seek repeated prosthetic treatment only when the condition of their existing dentures becomes critical, leading to compromised aesthetics and impaired chewing function. A key feature of repeated prosthetics is that the longer a patient has used a removable denture, the more ingrained their habits become with the old prosthesis, making adaptation to a new one more difficult. Breaking these habits and the established perception of the ideal comfortable denture is a challenging task. Therefore, when planning the design of a new prosthesis, it is essential to examine the previous removable denture thoroughly. When fabricating a new dental prosthesis, the characteristics of the previous one should be considered, while also restoring all lost functions. During repeated prosthetic treatment, patients adapt to new removable dentures with much more difficulty and at a slower pace.